Differences in the properties of disrupted and surviving satellites of Milky-Way-mass galaxies in relation to their host accretion histories - Grimozzi, Salvador Esteban (2024)
From the chemodynamical properties of tidal debris in the Milky Way, it has been inferred that the dwarf satellites that have been disrupted had different chemical abundances from their present-day counterparts of similar mass that survive today, specifically, they had lower [Fe/H] and higher [Mg/Fe]. Here we use the Artemis simulations to study the relation between the chemical abundances of disrupted progenitors of MW-mass galaxies and their stellar mass, and the evolution of the stellar mass–metallicity relations (MZR) of this population with redshift. We find that these relations have significant scatter, which correlates with the accretion redshifts (zacc) of satellites, and with their cold gas fractions. We investigate the MZRs of dwarf populations accreted at different redshifts and find that they have similar slopes, and also similar with the slope of the MZR of the surviving population (≈0.32). However, the entire population of disrupted dwarfs displays a steeper MZR, with a slope of ≈0.48, which can be explained by the changes in the mass spectrum of accreted dwarf galaxies with redshift. We find strong relations between the (mass-weighted) 〈zacc〉 of the disrupted populations and their global chemical abundances (〈[Fe/H]〉 and 〈[Mg/Fe]〉), which suggests that chemical diagnostics of disrupted dwarfs can be used to infer the types of merger histories of their hosts. For the case of the MW, our simulations predict that the bulk of the disrupted population was accreted at 〈zacc〉 ≈ 2, in agreement with other findings. We also find that disrupted satellites form and evolve in denser environments, closer to their hosts, than their present-day counterparts.